ANALISIS LOYALITAS KONSUMEN BERDASARKAN KUALITAS PRODUK DAN PROMOSI PADA MINUMAN TRADISIONAL BIR PLETOK BABEH BOYO JAKARTA - Yusup, Iskandar; Sulistiani, Sinta (Journal of Research and Publication Innovation, 2024)
This research aims to analyze product quality and marketing strategies towards consumer loyalty to the traditional beer Pletok